CRISPR Knockouts of pmela and pmelb Engineered a Golden Tilapia by Regulating Relative Pigment Cell Abundance. (4th June 2022) - Wang, Chenxu; Xu, Jia; Kocher, Thomas D; Li, Minghui; Wang, Deshou
Abstract: Premelanosome protein ( pmel ) is a key gene for melanogenesis. Mutations in this gene are responsible for white plumage in chicken, but its role in pigmentation of fish remains to be demonstrated. In this study, we found that most fishes have 2 pmel genes arising from the teleost-specific whole-genome duplication. Both pmela and pmelb were expressed at high levels in the eyes and skin of Nile tilapia. We mutated both genes in tilapia using CRISPR/Cas9. Homozygous mutation of pmela resulted in yellowish body color with weak vertical bars and a hypopigmented retinal pigment epithelium (RPE) due to significantly reduced number and size of melanophores. In contrast, we observed an increased number and size of xanthophores in mutants compared to wild-type fish. Homozygous mutation of pmelb resulted in a similar, but milder phenotype than pmela −/− mutants. Double mutation of pmela and pmelb resulted in loss of additional melanophores compared to the pmela −/− mutants, and also an increase in the number and size of xanthophores, producing a golden body color. The RPE pigmentation of pmela −/− ;pmelb −/− was similar to pmela −/− mutants, with much less pigmentation than pmelb −/− mutants and wild-type fish. Taken together, our results indicate that, although both pmel genes are important for the formation of body color in tilapia, pmela plays a more important role than pmelb. To our knowledge, this is the first report on mutation of pmelb or both pmela;pmelb in fish. Studies on these mutants suggest new strategies for breeding golden tilapia, and also provide a new model for studies of pmel function in vertebrates. Graphical Abstract: